A Review of Recently Developed LC–MS/MS Methods for the Analysis of Pharmaceuticals and Personal Care Products in Water. (29th January 2020) - Kachhawaha, Akanksha S; Nagarnaik, Pranav M; Labhasetwar, Pawan; Banerjee, Kaushik
Abstract: Background: Pharmaceuticals and personal care products (PPCPs) are present in the environment in trace concentrations. These compounds may cause health hazards to human beings and animals. The concerns related to their existence has led to development of a number of sensitive, accurate, and robust analytical methods. Objective: This article aims to review the recently developed chromatography-MS-based methods for the analysis of PPCPs in varied aqueous matrices and also presents a brief overview of the current status of PPCPs in the Indian aquatic environment. Methods: It demonstrates existing and recent trends in sampling, sample preparation techniques, and instrumentation methods for estimation of PPCPs in water. Results: Solid-phase extraction is found to be the most commonly used sample preparation technique, and LC–tandem MS (MS/MS; with electrospray ionization) is the most extensively used instrumentation technique for the analysis of PPCPs. Conclusions: The analytical methods reviewed here provide a detailed overview of the procedures for detection and quantification of PPCPs in water. These methods are useful for monitoring these compounds in environmental matrices and facilitate risk assessment studies. Highlights: This paper reviews the analytical methods for estimation of PPCPs in aquatic environmental matrices and presents their comprehensive evaluation.